Comparing Measurement Techniques of Accommodative Amplitude Among School Children. - Amiebenomo, Onyekachukwu M.; Ovenseri-Ogbomo, Godwin O.; Nwacheli, Chiedu (Optometry & Visual Performance, 2018)
Background: There is no consensus on the precise method of measuring amplitude of accommodation (AA) in routine clinical examination. In addition, studies have queried the use of Hofstetter's equation for computing the expected AA for different populations. This study was designed to compare four subjective methods of AA measurement in children and results from each method with Hofstetter's calculated average AA. Methods: An evenly distributed sample of 103 children aged 6-17 years attending schools in Benin City participated in this study. Amplitude of accommodation measurements--push-up (PU), push-down PD), minus lens to blur (MLB), and modified push-up (MPU)--were carried out in children with emmetropia. The values obtained for each method were compared with Hofstetter's calculated average values. Agreement among each method was investigated using Bland- Altman plots. Results: The means ± SD obtained for the right eye of subjects in Diopters (D) were: PU (12.69 ± 3.16), PD (12.50 ± 2.95), MLB (11.83 ± 2.99), and MPU (11.88 ± 2.88). Using the t-test, significant differences were found between all groups except the MLB and MPU pair. Hofstetter's calculated average differed significantly from results obtained using each method (P<0.0001). Bland-Altman plots showed levels of agreement between the PU and PD and the MLB and MPU methods. Conclusion: Given the difference in results between some of the measurement techniques and with Hofstetter's calculated average AA values, caution should be taken when making decisions concerning AA measurements and accommodative anomalies in school children aged 6-17 years in Benin-city, Nigeria.